Assessing the influence of calcium on X65 carbon steel pitting using an artificial pit. Issue 4 (26th November 2022) - Mohammed, Sikiru Adepoju; Hua, Yong; Barker, Richard
Abstract: Corrosion products that form on carbon steel in sweet (CO2 ) environments can protect the steel by retarding interactions between the substrate steel and a corrosive electrolyte. Such protective films could become damaged at local sites leading to potential differences and the emergence of galvanic currents with the consequence of pitting in certain envfironments. The large protected surface (with a higher positive potential) becomes a cathode while the tiny exposed surface (with a lower positive potential) becomes the anode. Films formed in a Ca 2+ ‐rich environment often comprise mixed calcium and iron carbonates in the form, Ca x Fe(1− x ) CO3 . This work utilized an artificial pit to investigate pitting under Ca x Fe(1− x ) CO3 film conditions. Mixed carbonate films were grown on cathode discs (25‐mm diameter) for 96 h at pH 7.5, 50°C. Freshly polished anode pins were screwed onto the cathode disc and the galvanic currents were measured for 24 h. The anode/cathode area ratios were varied by using pins of 1, 2, and 3 mm diameter. Scanning electron microscope, X‐ray powder diffraction, and energy‐dispersive X‐ray were employed to examine the electrode surfaces after the test while surface profilometry was conducted to obtain pit profiles on the anode pins. Galvanic current increased with the addition of 682 ppm Ca 2+ to the solution while pseudopassivation occurred under mixed calcium–iron carbonate films. The galvanic current was observed to drop as corrosion products formed on the anode electrode. Profilometry revealed the emergence of pits on the anode electrode. The pitting threshold was commensurate with the magnitude of the galvanic current density recorded. Abstract : A research work that unravels the relationship between galvanic current and pitting threshold as well as pseudo‐passivation in calcium‐rich solutions using a novel artificial pit design. Corrosion products that form on steel surfaces also grow within pits while micro‐level stochastic pits emerge beneath the film on the pit anode. Calcium presence increases the galvanic current between film‐covered and compromised spots in low‐carbon steel.